Hierarchical hollow carbon spheres: Novel synthesis strategy, pore structure engineering and application for micro-supercapacitor. (February 2020) - Yang, Xiaodan; Li, Yongliang; Zhang, Peixin; Sun, Lingna; Ren, Xiangzhong; Mi, Hongwei
Abstract: Hollow carbon spheres (HCSs) have attracted great attention for their unique structure, but they perform unsatisfactory rate capacity for lack of mesopore. Here, we propose a novel strategy for fabricating the HCSs with macro-meso-microporous hierarchical pore structure, without etching and alkali activation. Our results show that HCSs can deliver a high gravimetric energy density of 6.2 Wh·kg −1 at the power density of 25 W·kg −1, as well as the energy density reaches up to 3.6 Wh·kg −1 at a high power density of 2.2 kW·kg −1 . Moreover, assembled into micro-supercapacitor, HCSs perform a high areal capacitance of 15.4 mF·cm −2  at 0.2 mA·cm −2 . Such excellent electrochemical performances of HCSs should be ascribed to the well-balanced pore distribution, which have been revealed by the electrochemical impedance spectroscopy and equivalent series resistance. It is believed that such advanced hollow carbonaceous materials are not only suitable for supercapacitors, but also be expected to apply for Li–S battery, sensor and drug delivery. Graphical abstract: Image 1